Improved Ability To Study Persuasion Structure Using The Student Teams Achievement Division Learning Model - Petrus Martua Zendrato; Riana Riana; Yanida Bu'ulolo (Universitas Muhammadiyah Enrekang, 2022)
This study aims to improve students' ability to study the structure of persuasion texts using the Student Teams Achievement Division learning model. The subjects of this study were 25 students of class VIII-A of SMP Negeri 2 Gunungsitoli Utara, totaling 25 students, 8 male students and 17 female students. This study uses a Classroom Action Research model with the implementation procedures of planning, action, observation, and reflection. This research activity was carried out in two cycles using data collection techniques, observation sheets, and assessment sheets. Based on the results of the study, there was an increase in the ability of students to study the structure of persuasion texts using the Student Teams Achievement Division learning model. It can be seen in the results of the first cycle that the lowest value is 43.75, and the highest is 75, with an average value of 57.25. In contrast, the second cycle obtained the lowest value of 56.25 and the highest of 93.75. Based on the study results, it can be concluded that the Student Teams Achievement Division learning model can improve students' ability to study the structure of persuasion texts for class VIII-A students of SMP Negeri 2 Gunungsitoli Utara.